2020
DOI: 10.1039/d0ra00464b
|View full text |Cite
|
Sign up to set email alerts
|

Spin relaxation induced by interfacial effects in n-GaN/MgO/Co spin injectors

Abstract: The interface-related spin relaxation in n-GaN/MgO/Co was investigated by both electrical Hanle effect and time resolved Kerr rotation spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…For structures with an in-plane magnetization, an increase of the electron spin polarization under an external magnetic field parallel to the electron spin was reported [25,28]. This phenomenon was named inverted Hanle effect, in contrast to the regular Hanle effect and attributed to the compensation of static random stray fields, produced near the FM layer due to the interface roughness.…”
mentioning
confidence: 99%
“…For structures with an in-plane magnetization, an increase of the electron spin polarization under an external magnetic field parallel to the electron spin was reported [25,28]. This phenomenon was named inverted Hanle effect, in contrast to the regular Hanle effect and attributed to the compensation of static random stray fields, produced near the FM layer due to the interface roughness.…”
mentioning
confidence: 99%
“…It can be observed that the I-V characteristics of the GaN/Co Schottky junction exhibit a non-linear and symmetric behavior. Rowell criteria were applied to determine the tunneling process [18] . First, the conductance of the tunneling junctions should have a parabolic dependence on the applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…The LSV device has two CFAS/n + -GaN contacts for spin injection and detection, and two Au/Ti ohmic contacts are formed at the ends of the n + -GaN layer. [24,28] The two-different shaped CFAS/GaN contacts (FM1 and FM2) were also connected to Au/Ti bonding pads to measure the spin transport through the n + -GaN layer. Before the spintransport measurements, we confirmed the current-voltage (I-V) characteristics of the CFAS/n + -GaN interfaces, as presented in Figure 5c, at 50-300 K. Here, the I-V characteristics of the CFAS/n + -GaN interface were evaluated by three-terminal methods, as illustrated in the inset.…”
Section: Spin Transport In Ganmentioning
confidence: 99%
“…Thus far, it has been demonstrated, even at room temperature, electrical spin injection into GaN in LED structures [20][21][22][23] and three-or four-terminal lateral device structures. [23][24][25][26][27][28][29] However, almost all of the previous related studies have used an insulating tunnel barrier such as MgO and AlN for electrical spin injection into GaN to solve the spin resistance mismatch problem, [30][31][32] resulting in high-resistance contacts with a resistance-area product (RA) higher than several MΩμm 2 . [20,21,29] If such high-resistance contacts were utilized, they would limit the future use of GaN in applications such as medical spin LEDs, [33] and spin-polarized lasers (spin lasers) for ultrafast switches, high-performance reconfigurable interconnects, and secure communications on chips.…”
Section: Introductionmentioning
confidence: 99%